Postnatal foot length of newborn: its correlation with gestational maturity - S., Srinivasa; C. A., Anjum Aara; Kalla, Pavan Kumar (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal death is one of the major contributors (50%) of Under-five child mortality and 70% of the infant mortality. The main causes of neonatal deaths are prematurity and low birth weight (LBW). This study was undertaken to assess newborn foot length and determine its usefulness in identifying LBW/Preterm Babies. Methods: This is a cross sectional hospital based study of 173 newborn babies, done in KIMS Hospital, Bengaluru. All live newborn infants were included in the study. Newborn babies with lower limb congenital anomalies were excluded from the study. Results: Out of 173 newborn, 99 babies were male (57%) and 74 were female (43%). 122 (70.5%) were term and 51(29.5%) were preterm. 48 (38%) were SGA, 120 (69%) were AGA and 5 (3%) were LGA. Their gestational age ranged from 28 to 40 weeks. In this study positive Correlation between foot length and gestational age was found with the “r” value of 0.823. The study also showed a positive correlation between foot length and weight with the “r” value of 0.831. Conclusions: This study has a good correlation of Foot length with gestational maturity and birth weight. Foot length of 7.45cm can be used as a cut- off point for differentiating between term and preterm babies. Derived equation from this study can be used by ASHAs and Anganwadi workers for the estimation of gestational age in resource poor situations and refer the preterm newborns to higher centres for further management as early as possible to prevent long and short term complications of prematurity.